Orthodontic appliance coating and preparation method thereof

By forming a multi-layer structural coating on the orthodontic device, combining polydopamine and bioactive glass nanoparticles and Mxene nanosheets, the problems of enamel demineralization and metal corrosion are solved, and better corrosion resistance and remineralization are achieved The effect of the correction device improves the efficiency of the use and treatment effect.

CN119242167APending Publication Date: 2025-01-03AFFILIATED STOMATOLOGICAL HOSPITAL OF NANCHANG UNIV (JIANGXI PROVINCIAL STOMATOLOGICAL HOSPITAL)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411325930.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Orthodontic appliances are prone to demineralization of enamel and corrosion of metal materials during use. The prior art is difficult to effectively prevent these problems, especially incomplete cleaning of brackets and neck areas, resulting in tooth decay and increased friction.

Method used

Using a coating composed of a multi-layer structure, including a first polydopamine layer, a bioactive glass nanoparticle layer, a Mxene nanosheet layer and a third polydopamine layer, these layers are bonded and fixed by polydopamine to form durable and corrosion-resistant The coating is prepared by combining sandpaper treatment and ultrasonic cleaning.

Benefits of technology

It significantly improves the remineralization effect and corrosion resistance, reduces the occurrence of dental surface demineralization and caries, reduces the friction between metal materials, and improves the use efficiency and treatment effect of orthodontic remediation devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242167A_ABST
    Figure CN119242167A_ABST
Patent Text Reader

Abstract

The invention relates to the field of chemical coatings, in particular to an orthodontic appliance coating and a preparation method thereof. An orthodontic appliance coating comprises a first polydopamine layer, a bioactive glass nanoparticle layer, a second polydopamine layer, an Mxene nanosheet layer and a third polydopamine layer from bottom to top, and the orthodontic appliance coating is good in corrosion resistance and remineralization ability. The preparation method is simple, easy to operate, good in repeatability and suitable for industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of chemical coatings, and in particular to an orthodontic appliance coating and a preparation method thereof. Background Art

[0002] As a modern method of treating and reshaping teeth, orthodontic appliances work by generating force, or the functional force of the masticatory muscles and perioral muscles, to change the deformed jaw, misaligned teeth and periodontal supporting tissues through the appliance, so as to facilitate the normal growth and development of the maxillofacial region. The appliance is usually a mechanical device combined with an elastic metal wire and a bracket, or a plastic base, which is worn in the mouth or maxillofacial region.

[0003] During the treatment period of an average of more than two years, enamel demineralization and metal material corrosion are prone to occur. Enamel demineralization is often regarded as the earliest sign of caries. Studies have shown that more than one-third of patients experience enamel demineralization during orthodontic treatment. Enamel demineralization during orthodontic treatment is most common in maxillary lateral incisors, followed by mandibular canines and first molars, mainly involving the area between the bracket and the neck of the tooth. This is mainly because these areas are often placed with traction hooks and elastic traction devices, making it difficult to clean them deeply and thoroughly.

[0004] Therefore, it is usually necessary to coat the orthodontic appliance with a layer of anti-corrosion and mineralization-promoting materials. Chinese Patent 202311543819.8 discloses a graphene oxide composite nanocoating. The graphene oxide composite nanocoating obtained by the present invention overcomes the problem that G0 alone is easy to agglomerate. It not only has the advantages of long-term antibacterial, strong corrosion resistance, and low toxicity, but also has a good remineralization effect on tooth enamel, can reduce the occurrence of tooth surface demineralization and caries, and effectively reduce the friction between dental metal materials, especially the friction between metal materials used in oral orthodontics, which is beneficial to the sliding between the archwire and the bracket groove during the orthodontic process, thereby helping to improve the efficiency of orthodontic correction of aligning and leveling the teeth and shorten the course of treatment. Summary of the invention

[0005] Based on this, an object of the present invention is to provide an orthodontic appliance coating, which has good corrosion resistance and good remineralization effect on teeth; another object of the present invention is to provide an orthodontic appliance coating and a preparation method thereof, which method is simple, easy to operate, has good repeatability, and is suitable for industrialization.

[0006] An orthodontic appliance coating comprises, from bottom to top, a first polydopamine layer, a bioactive glass nanoparticle layer, a second polydopamine layer, a Mxene nanosheet layer and a third polydopamine layer, with thicknesses of 0.5 μm, 0.5-1.5 μm, 0.5 μm, 0.5-1.5 μm and 0.5 μm, respectively.

[0007] The combination of bioactive glass nanoparticle layer and Mxene nanosheet layer makes the orthodontic appliance coating have strong remineralization ability and good corrosion resistance. Three layers of dopamine are used to bond and fix the bioactive glass nanoparticle layer and Mxene nanosheet layer respectively, making the coating more durable.

[0008] The method for preparing an orthodontic appliance coating comprises the following steps: (1) treating the surface of an orthodontic appliance with polydopamine to form a first polydopamine layer; (2) bonding a bioactive glass nanoparticle layer to the orthodontic appliance after the polydopamine treatment and drying; (3) bonding a second polydopamine layer to the dried orthodontic appliance; (4) bonding a Mxene nanosheet layer to the second polydopamine layer; and (5) bonding a third polydopamine layer to the Mxene nanosheet layer.

[0009] Furthermore, in step (1), the surface of the orthodontic appliance is polished with sandpaper, polished on a polishing machine, ultrasonically cleaned, and then the surface oxide film is removed, cleared, dried, and immersed in a 5 mg / ml dopamine hydrochloride ethylenediaminetetraacetic acid buffer solution for 12 hours, cleaned, and dried to obtain an orthodontic appliance with a first polydopamine layer. The polydopamine solution has a pH value of 8-10 and a temperature of 25°C.

[0010] Furthermore, the preparation steps of the bioactive glass nanoparticles in step (2) include: (21) dissolving PEG in deionized water; (22) adding ethyl acetate to the PEG aqueous solution, adding ammonia water, and adjusting the pH value to 8.5; (23) adding tetraethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate under ultrasonic stirring, and reacting for 4-6 hours; and (24) centrifuging the reaction product, washing, drying and calcining to prepare mesoporous bioactive glass nanoparticles.

[0011] Furthermore, in step (2), the bioactive glass nanoparticles are dissolved in a PEG solution, and the solution is added dropwise to the orthodontic appliance having the first polydopamine layer obtained in step (1), and then dried.

[0012] Furthermore, step (3) is to immerse the orthodontic appliance dried in step (2) in a 5 mg / ml dopamine hydrochloride ethylenediaminetetraacetic acid buffer solution for 12 hours, wash, and dry to obtain an orthodontic appliance having a second polydopamine layer.

[0013] Furthermore, the preparation method of the Mxene nanosheet layer in step (4) comprises the following steps: mixing Ti2AlC and a hydrofluoric acid solution, and etching to obtain Mxene; mixing the Mxene and a tetrabutylammonium hydroxide solution, and subjecting the Mxene to electrostatic adsorption and ultrasonic treatment to obtain exfoliated Mxene nanosheets; and mixing the Mxene nanosheets with an aqueous solution of 1-butyl-3-methylimidazolium tetrafluoroborate under a protective atmosphere to obtain Mxene composite nanosheets.

[0014] Furthermore, the Mxene composite nanosheet obtained in step (4) is dissolved in a PEG solution, added dropwise to the orthodontic appliance having the second polydopamine layer obtained in step (3), and dried.

[0015] Furthermore, in step (5), the orthodontic appliance obtained in step (4) is immersed in a 5 mg / ml dopamine hydrochloride ethylenediaminetetraacetic acid buffer solution for 12 hours, washed, and dried to obtain an orthodontic appliance having a third polydopamine layer.

[0016] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 These are SEM photos of coating examples 1-5 and comparative example samples after corrosion resistance testing. DETAILED DESCRIPTION

[0018] Example 1

[0019] An orthodontic appliance coating comprises, from bottom to top, a polydopamine layer, a bioactive glass nanoparticle layer, a polydopamine layer, a Mxene nanosheet layer and a polydopamine layer, with thicknesses of 0.5 μm, 1 μm, 0.5 μm, 1 μm and 0.5 μm, respectively.

[0020] The method for preparing an orthodontic appliance coating comprises the following steps: (1) treating the surface of an orthodontic appliance with polydopamine to form a first polydopamine layer; (2) bonding a bioactive glass nanoparticle layer to the orthodontic appliance after the polydopamine treatment and drying; (3) bonding a second polydopamine layer to the dried orthodontic appliance; (4) bonding a Mxene nanosheet layer to the second polydopamine layer; and (5) bonding a third polydopamine layer to the Mxene nanosheet layer.

[0021] Furthermore, in step (1), the surface of the orthodontic appliance is polished with sandpaper, polished on a polishing machine, ultrasonically cleaned, and then the surface oxide film is removed, cleared, dried, and immersed in a 5 mg / ml dopamine hydrochloride ethylenediaminetetraacetic acid buffer solution for 12 hours, cleaned, and dried to obtain an orthodontic appliance with a first polydopamine layer. The polydopamine solution has a pH value of 8-10 and a temperature of 25°C.

[0022] Furthermore, the steps for preparing the bioactive glass nanoparticle layer in step (2) include: (21) dissolving 5g PEG in 100ml deionized water; (22) adding 8ml ethyl acetate to the PEG aqueous solution, adding ammonia water, and adjusting the pH value to 8.5; (23) adding 5ml tetraethyl orthosilicate, 0.5ml triethyl phosphate and 3.5g calcium nitrate tetrahydrate under ultrasonic stirring, and reacting for 6 hours; and (24) centrifuging, washing, drying and calcining the reaction product for 6h to obtain mesoporous bioactive glass nanoparticles, wherein the calcination temperature is 600°C.

[0023] Furthermore, in step (2), 5 g of bioactive glass nanoparticles are dissolved in 20 ml of PEG solution, and the solution is added dropwise to the orthodontic appliance having the first polydopamine layer obtained in step (1), and then dried.

[0024] Furthermore, step (3) is to immerse the orthodontic appliance dried in step (2) in a 5 mg / ml dopamine hydrochloride ethylenediaminetetraacetic acid buffer solution for 12 hours, wash, and dry to obtain an orthodontic appliance having a second polydopamine layer.

[0025] Furthermore, the preparation method of the Mxene nanosheet layer in step (4) includes the following steps: mixing 5g Ti2AlC and 5ml hydrofluoric acid solution, etching to obtain an Mxene solution, adding 10ml tetrabutylammonium hydroxide solution to mix, ultrasonically obtaining peeled Mxene nanosheets, and then adding 10ml 1-butyl-3-methylimidazolium tetrafluoroborate aqueous solution to mix to obtain Mxene composite nanosheets.

[0026] Furthermore, 5 g of the Mxene composite nanosheets obtained in step (4) are dissolved in 20 ml of PEG solution, added dropwise to the orthodontic appliance having the second polydopamine layer obtained in step (3), and dried.

[0027] Furthermore, in step (5), the orthodontic appliance obtained in step (4) is immersed in a 5 mg / ml dopamine hydrochloride ethylenediaminetetraacetic acid buffer solution for 12 hours, washed, and dried to obtain an orthodontic appliance having a third polydopamine layer.

[0028] The only difference between Example 2 and Example 1 is: an orthodontic appliance coating, comprising, from bottom to top, a polydopamine layer, a bioactive glass nanoparticle layer, a polydopamine layer, a Mxene nanosheet layer and a polydopamine layer, whose thicknesses are 0.5 μm, 1.5 μm, 0.5 μm, 1.5 μm and 0.5 μm, respectively.

[0029] Step (2) dissolving 7 g of bioactive glass nanoparticles in 20 ml of PEG solution, adding the solution dropwise to the orthodontic appliance having the first polydopamine layer obtained in step (1), and drying the solution.

[0030] The preparation method of the Mxene nanosheet layer in step (4) comprises the following steps: mixing 7g Ti2AlC and 5ml hydrofluoric acid solution, etching to obtain a Mxene solution, adding 10ml tetrabutylammonium hydroxide solution to mix, ultrasonically obtaining peeled Mxene nanosheets, and then adding 10ml 1-butyl-3-methylimidazolium tetrafluoroborate aqueous solution to mix to obtain Mxene composite nanosheets.

[0031] Furthermore, 7 g of the Mxene composite nanosheets obtained in step (4) are dissolved in 20 ml of PEG solution, added dropwise to the orthodontic appliance having the second polydopamine layer obtained in step (3), and dried.

[0032] The only difference between Example 3 and Example 1 is: an orthodontic appliance coating, comprising, from bottom to top, a polydopamine layer, a bioactive glass nanoparticle layer, a polydopamine layer, a Mxene nanosheet layer and a polydopamine layer, whose thicknesses are 0.5 μm, 0.5 μm, 0.5 μm, 0.5 μm and 0.5 μm, respectively.

[0033] Step (2) dissolving 3 g of bioactive glass nanoparticles in 20 ml of PEG solution, dropping the solution onto the orthodontic appliance having the first polydopamine layer obtained in step (1), and drying the solution.

[0034] The preparation method of the Mxene nanosheet layer in step (4) comprises the following steps: mixing 4g Ti2AlC and 5ml hydrofluoric acid solution, etching to obtain a Mxene solution, adding 10ml tetrabutylammonium hydroxide solution to mix, ultrasonically obtaining exfoliated Mxene nanosheets, and then adding 10ml 1-butyl-3-methylimidazolium tetrafluoroborate aqueous solution to mix to obtain Mxene composite nanosheets.

[0035] Furthermore, 4 g of the Mxene composite nanosheet obtained in step (4) is dissolved in 20 ml of PEG solution, added dropwise to the orthodontic appliance having the second polydopamine layer obtained in step (3), and dried.

[0036] The only difference between Example 4 and Example 1 is: an orthodontic appliance coating, comprising, from bottom to top, a polydopamine layer, a bioactive glass nanoparticle layer, a polydopamine layer, a Mxene nanosheet layer and a polydopamine layer, whose thicknesses are 0.5 μm, 0.8 μm, 0.5 μm, 0.8 μm and 0.5 μm, respectively.

[0037] Step (2) dissolving 4.5 g of bioactive glass nanoparticles in 20 ml of PEG solution, adding the solution dropwise to the orthodontic appliance having the first polydopamine layer obtained in step (1), and drying the solution.

[0038] The preparation method of the Mxene nanosheet layer in step (4) comprises the following steps: mixing 4.5 g Ti2AlC and 5 ml hydrofluoric acid solution, etching to obtain a Mxene solution, adding 10 ml tetrabutylammonium hydroxide solution to mix, ultrasonically obtaining exfoliated Mxene nanosheets, and then adding 10 ml 1-butyl-3-methylimidazolium tetrafluoroborate aqueous solution to mix to obtain Mxene composite nanosheets.

[0039] Furthermore, 7 g of the Mxene composite nanosheets obtained in step (4) are dissolved in 20 ml of PEG solution, added dropwise to the orthodontic appliance having the second polydopamine layer obtained in step (3), and dried.

[0040] The only difference between Example 5 and Example 1 is: an orthodontic appliance coating, comprising, from bottom to top, a polydopamine layer, a bioactive glass nanoparticle layer, a polydopamine layer, a Mxene nanosheet layer and a polydopamine layer, whose thicknesses are 0.5 μm, 1.2 μm, 0.5 μm, 1.2 μm and 0.5 μm, respectively.

[0041] Step (2) dissolving 5.5 g of bioactive glass nanoparticles in 20 ml of PEG solution, adding the solution dropwise to the orthodontic appliance having the first polydopamine layer obtained in step (1), and drying the solution.

[0042] The preparation method of the Mxene nanosheet layer in step (4) comprises the following steps: mixing 6g Ti2AlC and 5ml hydrofluoric acid solution, etching to obtain a Mxene solution, adding 10ml tetrabutylammonium hydroxide solution to mix, ultrasonically obtaining peeled Mxene nanosheets, and then adding 10ml 1-butyl-3-methylimidazolium tetrafluoroborate aqueous solution to mix to obtain Mxene composite nanosheets.

[0043] Furthermore, 6 g of the Mxene composite nanosheets obtained in step (4) are dissolved in 20 ml of PEG solution, added dropwise to the orthodontic appliance having the second polydopamine layer obtained in step (3), and dried.

[0044] test:

[0045] Mineral regeneration test: The demineralized enamel slices were immersed in artificial saliva at 37°C for 15 days together with the uncoated stainless steel brackets (comparative example) and the coated stainless steel brackets of Examples 1-5, and then taken out, ultrasonically cleaned with deionized water for 10 minutes, and dried for testing.

[0046] Use a microhardness tester to test the microhardness of six dried samples. Place the samples on the test bench, take 4 points, apply a vertical load of 200g for 10 seconds, and calculate the average value of the 4 points as the hardness value of the sample. The data is as follows:

[0047] sample Comparative Example Example 1 Example 2 Example 3 Example 4 Example 5 Hardness average value 152 183 182 185 183 181 First point value 150 181 184 185 186 183 Second point value 152 184 180 186 185 182 The third point value 154 185 182 184 180 179 Fourth point value 152 182 182 185 181 180

[0048] It can be seen from the above table that the five example samples of the present application exhibited an obvious remineralization effect.

[0049] Corrosion resistance test: The uncoated stainless steel bracket and the coated stainless steel bracket of Examples 1-5 were welded with copper wire and encapsulated with a ring resin as the working electrode in the three-electrode system. The electrolyte was artificial saliva and the external water bath was kept at a constant temperature of 37°C. The surface of the sample was observed by SEM photography. The results are shown in the attached figure. Figure 1 .

[0050] It is obvious from the SEM photos that the stainless steel bracket without coating has cracks, while the stainless steel bracket coated with coating of Examples 1-5 has no cracks after immersion.

[0051] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.

Claims

1. An orthodontic appliance coating, characterized in that: It includes, from bottom to top, a first polydopamine layer, a bioactive glass nanoparticle layer, a second polydopamine layer, a Mxene nanosheet layer and a third polydopamine layer.

2. The orthodontic appliance coating according to claim 1, characterized in that: The thicknesses of the first polydopamine layer, the bioactive glass nanoparticle layer, the second polydopamine layer, the Mxene nanosheet layer and the third polydopamine layer are 0.5 μm, 0.5-1.5 μm, 0.5 μm, 0.5-1.5 μm and 0.5 μm, respectively.

3. The method for preparing an orthodontic appliance coating according to claim 1 or 2, characterized in that: The method for preparing an orthodontic appliance coating comprises the following steps: (1) treating the surface of an orthodontic appliance with polydopamine to form a first polydopamine layer; (2) bonding a bioactive glass nanoparticle layer to the orthodontic appliance after the polydopamine treatment and drying; (3) bonding a second polydopamine layer to the dried orthodontic appliance; (4) bonding a Mxene nanosheet layer to the second polydopamine layer; and (5) bonding a third polydopamine layer to the Mxene nanosheet layer.

4. The method for preparing an orthodontic appliance coating according to claim 3, characterized in that: In the step (1), the surface of the orthodontic appliance is polished with sandpaper, polished on a polishing machine, and then ultrasonically cleaned, and then the surface oxide film is removed, and after cleaning and drying, it is immersed in a 5 mg / ml dopamine hydrochloride ethylenediaminetetraacetic acid buffer solution for 12 hours, cleaned and dried to obtain an orthodontic appliance with a first polydopamine layer, wherein the dopamine hydrochloride ethylenediaminetetraacetic acid buffer solution has a pH value of 8-10 and a temperature of 25°C.

5. The method for preparing an orthodontic appliance coating according to claim 4, characterized in that: The preparation steps of the bioactive glass nanoparticles in step (2) include: (21) dissolving PEG in deionized water; (22) adding ethyl acetate to the PEG aqueous solution, adding ammonia water, and adjusting the pH value to 8.5; (23) adding tetraethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate under ultrasonic stirring, and reacting for 4-6 hours; and (24) centrifuging, washing, drying and calcining the reaction product to obtain porous bioactive glass nanoparticles.

6. The method for preparing an orthodontic appliance coating according to claim 4, characterized in that: Step (2) dissolving the bioactive glass nanoparticles in the PEG solution, dropping the solution onto the orthodontic appliance having the first polydopamine layer obtained in step (1), and drying the solution.

7. The method for preparing an orthodontic appliance coating according to claim 6, characterized in that: Step (3) is to immerse the orthodontic appliance dried in step (2) into a 5 mg / ml dopamine hydrochloride ethylenediaminetetraacetic acid buffer solution for 12 hours, wash, and dry to obtain an orthodontic appliance with a second polydopamine layer.

8. The method for preparing an orthodontic appliance coating according to claim 7, characterized in that: The preparation method of the Mxene nanosheet layer in step (4) comprises the following steps: mixing Ti2AlC and a hydrofluoric acid solution, and etching to obtain Mxene; mixing the Mxene and a tetrabutylammonium hydroxide solution, and ultrasonically obtaining exfoliated Mxene nanosheets; and mixing the Mxene nanosheets with an aqueous solution of 1-butyl-3-methylimidazolium tetrafluoroborate under a protective atmosphere to obtain Mxene composite nanosheets.

9. The method for preparing an orthodontic appliance coating according to claim 7, characterized in that: In step (4), the obtained Mxene composite nanosheets are dissolved in a PEG solution, added dropwise to the orthodontic appliance having a second polydopamine layer obtained in step (3), and dried.

10. The method for preparing an orthodontic appliance coating according to claim 9, characterized in that: Step (5) immersing the orthodontic appliance obtained in step (4) into a 5 mg / ml dopamine hydrochloride ethylenediaminetetraacetic acid buffer solution for 12 hours, washing, and drying to obtain an orthodontic appliance having a third polydopamine layer.

Citation Information

Patent Citations

  • Tooth remineralisation

    CN102245153A

  • Method for fixing functional molecules on biomedical material surface with dopamine serving as bridging

    CN102813963A

  • Nanometer functionalization surface modification method based on o-dihydroxybenzene derivatives

    CN103435829A

  • Tooth orthodontic device

    CN218045399U

  • Cathode material solvent condensate collection equipment

    KR1020250082221A